The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/2040-7378-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of circulatory shock and cerebral ischemia injury in heat stroke by combination treatment with dexamethasone and hydroxyethyl starch

Abstract: BackgroundIncreased systemic cytokines and elevated brain levels of monoamines, and hydroxyl radical productions are thought to aggravate the conditions of cerebral ischemia and neuronal damage during heat stroke. Dexamethasone (DXM) is a known immunosuppressive drug used in controlling inflammation, and hydroxyethyl starch (HES) is used as a volume-expanding drug in cerebral ischemia and/or cerebral injury. Acute treatment with a combined therapeutic approach has been repeatedly advocated in cerebral ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…Animals were then returned to their cages with free access to food and water [18][19][20][21]. The following day, they were heated in a water-bath at 38°C for 5 h [22,23]. This process was repeated every 2 days.…”
Section: A Murine Model Of Cerebral Ischemiamentioning
confidence: 99%
“…Animals were then returned to their cages with free access to food and water [18][19][20][21]. The following day, they were heated in a water-bath at 38°C for 5 h [22,23]. This process was repeated every 2 days.…”
Section: A Murine Model Of Cerebral Ischemiamentioning
confidence: 99%
“…Among several mechanisms proposed to give rise to heat stroke-induced brain injury, ischemia is thought to induce restricted diffusion. Ischemia of brain tissue results from attempts of the body's autoregulatory mechanisms to divert blood flow towards periphery to dissipate excessive heat (21,22). Increased intracranial pressure secondary to venous congestion and brain edema as the result of increased permeability of blood-brain or blood-cerebrospinal fluid barrier may also…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have confirmed these findings in comparable rodent models of CHS (peak T core =~43.5 • C). For example, prior corticosteroid injection was shown to inhibit GI MT and improve survival [53][54][55], whereas indomethacin injection enhanced gross morphological GI hemorrhage and worsened survival [56]. Similarly, direct intravenous endotoxin injection prior to sub-lethal CHS in rodents (peak T core =~42-43 • C) unexpectedly led to fatalities in 40% of animals (versus 0% in controls; [57]), or best-case increased symptoms of multiple-organ injury [58].…”
Section: The Gi Exertional Heat Stroke Paradigmmentioning
confidence: 99%